The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1574-6968.2008.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

The type III secretion system-dependent repression of NF-κB activation to the intracellular growth of Edwardsiella tarda in human epithelial cells

Abstract: Edwardsiella tarda is a pathogen with a broad host range infecting animals and humans. We have reported recently that the type III secretion system (TTSS) is essential for intracellular replication of the bacterium in murine macrophages. The present study shows that the TTSS is also needed for intracellular growth of the bacterium in human epithelial cells (HEp-2). However, different from the previous microarray analyses on murine macrophages, upregulation of the mRNA expression level of NF-kappaB target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…E. tarda prefers an intracellular lifestyle during infection in either epithelial (21,22) or phagocytic (15,23,24) cells, which provide an intracellular niche for this pathogen. In this study, we established an E. tarda infection model in murine macrophage-like cell line J774A.1.…”
Section: Resultsmentioning
confidence: 99%
“…E. tarda prefers an intracellular lifestyle during infection in either epithelial (21,22) or phagocytic (15,23,24) cells, which provide an intracellular niche for this pathogen. In this study, we established an E. tarda infection model in murine macrophage-like cell line J774A.1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when one of the two T3SS-regulatory genes, esrB and esrC, was deleted in E. tarda PPD130/91, the LD 50 s of the resulting mutants were 3 log units higher than that of the wild type (43,56). Although it has been speculated that Edwardsiella effectors may be responsible for the intracellular growth of the bacteria in HEp-2 cells (34) and for their multiplication in murine and fish macrophages (33,45), no T3SS effectors of E. tarda have been identified yet. In this study, we have identified the first effector of E. tarda, EseG.…”
Section: Discussionmentioning
confidence: 99%
“…The T3SS facilitates the survival of E. tarda in phagocytes and HEp-2 cells (19,33,34,45) and contributes to virulence in vivo (45). The deletion of various single T3SS genes, such as escC, eseB, eseD, or escA, increased the 50% lethal dose (LD 50 ) by approximately 1 log unit in blue gourami (49,55).…”
mentioning
confidence: 99%
“…Deletion of its T3SS ATPase gene esaN increased the 50% lethal dose (LD 50 ) by approximately 1 log in the blue gourami infection model (5). The T3SS facilitates the survival and replication of different E. tarda isolates in different eukaryotic cells, such as Hep-2 epithelial cells (6), the epithelioma papillosum of carp cells (3), J774A.1 macrophages (4), and fish primary macrophages (3,7).…”
mentioning
confidence: 99%